Circulating Tumor Cells Dynamics in Pancreatic Adenocarcinoma Correlate With Disease Status: Results of the Prospective CLUSTER Study. Issue 3 (September 2018) - Gemenetzis, Georgios; Groot, Vincent P.; Yu, Jun; Ding, Ding; Teinor, Jonathan A.; Javed, Ammar A.; Wood, Laura D.; Burkhart, Richard A.; Cameron, John L.; Makary, Martin A.; Weiss, Matthew J.; He, Jin; et al.
Abstract : Objectives: Previous retrospective studies demonstrated that circulating tumor cells (CTCs) subtypes correlate with overall survival in patients with pancreatic ductal adenocarcinoma (PDAC). Herein, we report results of a prospective observational study on CTCs dynamics to assess their clinical significance. Methods: The CLUSTER study is a prospective longitudinal study on PDAC CTCs dynamics (NCT02974764). Multiple peripheral blood samples were collected from 200 consecutively enrolled patients with presumed PDAC diagnosis. CTCs were isolated and characterized by immunofluorescence. Results: Two major CTCs subtypes were identified in PDAC patients: epithelial CTCs (eCTCs) and epithelial/mesenchymal CTCs (mCTCs). Patients who received neoadjuvant chemotherapy had significantly lower total CTCs (tCTCs, P = 0.007), eCTCs ( P = 0.007), and mCTCs ( P = 0.034), compared with untreated patients eligible for upfront resection. Surgical resection of the primary tumor resulted in significant reduction, but not disappearance, of CTCs burden across all cell subtypes ( P < 0.001). In multivariable logistic regression analysis, preoperative numbers of all CTCs subpopulations were the only predictors of early recurrence within 12 months from surgery in both chemo-naive and post-neoadjuvant patients (odds ratio 5.9 to 11.0). Alterations in CTCs were also observed longitudinally, before disease recurrence. A risk assessment score based on the difference of tCTCs increase accurately identified disease recurrence within the next 2 months, with an accuracy of 75% and 84% for chemo-naive and post-neoadjuvant patients, respectively. Conclusion: We report novel findings regarding CTCs from a large prospective cohort of PDAC patients. CTCs dynamics reflect progression of disease and response to treatment, providing important information on clinical outcomes, not available by current tumor markers and imaging. Abstract : Supplemental Digital Content is available in the text